Respuesta :

Answer:

[tex]\huge\boxed{9}[/tex]

Step-by-step explanation:

[tex]\sf (2^8 * 3^{-5} * 6^0)^{-2 } (\frac{3^{-2}}{2^3} )^4*2^{28}[/tex]

Rule of exponents [tex]a^0 = 1[/tex] , [tex]1/a^m = a^{-m}[/tex]

=> [tex]\sf 2^{8*-2} * 3 ^{-5*-2} * 3 ^{-2}* 2^{-3*4} * 2^{28}[/tex]

=> [tex]\sf 2 ^ {-16} * 3^{10} * 3^{-8} * 2 ^{-12}* 2^{28}[/tex]

Combining same bases

=> [tex]\sf 2 ^ {-16} * 2 ^{-12}* 2^{28}* 3^{10} * 3^{-8}[/tex]

When bases are same , powers are to be added

=> [tex]\sf 2 ^{-16-12+28} * 3^{10-8}[/tex]

=> [tex]\sf 2^{-28+28} * 3^2[/tex]

=> [tex]\sf 2^0 * 3^2[/tex]

=> [tex]\sf 3^2[/tex]

=> 9